‘Measuring’ the chronology of the so-called Moesian countermarks (Research Announcements "Heritage BG", 2025)
The study discusses the so-called Moesian countermarks. They are stamped in rectangularfields with the letters “TI CA” and “TICAE. The current text discusses two sites: the first is a military camp (ancient Almus), and the second (near modern Rasovo) is a civic settlement of the local inhabitants. Single coins from the time of the Flavians have been found at Almus, while at Rasovo such are totally lacking. The available data provided by the two sites demonstrates weak coin circulation during the time of Nero and of the Flavian dynasty. The authors believe this is the most likely time of circulation of the discussed countermarked coins. References:Banov, Petar. 2012. Kontramarkirani rimski bronzovi moneti ot I v. ot muzeya v Pleven. В: ΗPAKΛEOΥΣ ΣΩΘΡOΣ ΘAΣΙΩΝ [Hpakleoys Swthpos Thasiwn]. Studia in honorem Iliae Prokopov sexagenario ab amicis et discipulis dedicata, eds. Eugeni Paunov and Svetoslava Filipova, 489-501. Veliko Tarnovo.Dragoev, Deyan. 2024. Numizmatichniyat material ot rimskiya hram v m. Manastira, s. Shirokovo, obsht. Dve mogili. Izvestiya na Regionalen istoricheski muzey-Ruse No. 28, 306-321.Gencheva, Evgenia. 2002. Parviyat voenen lager v Novae, provintsiya Miziya (Severna Balgaria). Sofia-Warszawa.Gencheva, Evgenia. 2004. Rimskite fibuli ot Balgaria ot kraya na I v. pr. n. e. do kraya na VI v. ot n. e.. Veliko Tarnovo.Gerasimov, Todor. 1946. Antichnite moneti s kontramarki ot Dolna Miziya i Trakiya. Izvestiya na Balgarskiya arheologicheski institut No. 15: 51-81.Kabakchieva, Gergana. 2000. Oescus. Castra Oescensia. Rannorimski voenen lager pri ustieto na Iskar. Sofia.Stamberova, Miglena. 2023. Fibulite v Drevna Trakiya (V – I v. pr. Hr.). София.Almgren, Oscar. 1923. Studien über Nordeuropäische Fibelformen der ersten nachchristlichen Jahrhunderte mit Berücksichtigung der provinzial-römischen und südrussischen Formen. Mannus Bibliothek 32. Leipzig: Verlag von Curt Kabitzsch.Bojović, Dragoljub. 1983. Rimske fibule Singidunuma. Beograd.Božkova, Bistra. 1987. "Monete antiche di Ratiaria". Ratiariensia 3-4: 97-110.Ciołek, Renata, and Piotr Dyczek. 2011. Coins from Sector IV. Novae. Legionary fortress and Late Antique town 2. Warsaw.Cociş, Sorin. 2004. The Brooches from Roman Dacia. Cluj-Napoca.Kabakchieva, Gergana, and Sonia Lazarova. 2012. Ancient Military Fort and Customs. Dimum. Belene Town, Pleven region. Plovdiv.Martini, Rodolfo. 2002. Monete romane imperiali contromarcate di bronzo dell’area delle province della Moesia e della Thracia. Vol. 1. Milano.Martini, Rodolfo. 2003. Monete romane imperiali contromarcate di bronzo dall’area delle province della Moesia e della Thracia di 1. secolo D.C. Vol. 2. Milano.Martini, Rodolfo, and Evgeni Paunov. 2004. "Early Roman imperial countermarked coins from Moesia: first critical observations (typology, frequency, chronology and analysis of distribution)". В: Numismatic and Sphragistic Contributions to History of the Western Black Sea coast. International Conference, Varna, 12 – 15 September 2001, 159-174.Miškec, Alenka. 2005. "Some aspects of countermarked coins from the time of the Julio-Claudian dynasty in Pannonia". В: XIII Congreso Internacional de Numismatica. Madrid 2003. Actes I, eds. Carmen Alfaro, Carmen Marcos, and Paloma Otera, 1005-1011. Madrid.Paunov, Evgeni. 2021. From Koine to Romanitas. The Numismatic Evidence for Roman Expansion and Settlement in Moesia and Thrace (ca. 146 BC – AD 98/117). Volume 1. Antiquitates. Archäologische Forschungsergebnisse. Band 76.1. Hamburg.Riha, Emilie. 1979. Die römischen Fibeln aus Augst und Kaiseraugst. Forschungen in Augst 3. Augst.Rustoiu, Aurel. 1997. Fibulele din Dacia preromană (sec. II о.e.n. - I e.n.). Bibliotheca Thracologica XXII. Bucureşti.Vagalinski, Lyudmil. 2011. "Light Industry in Roman Thrace: The Case of lime production". В: Early Roman Thrace. New evidence from Bulgaria, 40-58. Portsmouth, Rhode Island.Vladimirova-Aladjova, Dochka. 1999. "Countermarked Roman Coins from Lower Danube". Macedonian Numismatic Journal 3: 45-49.Zhivkov, Vladislav. 2023. "Hoard of bronze trulla from Almus and the Dacian wars of Domitian". В: The Roman provincial society in Lower Danube. (Studia academica Šumenensia X), 30-52. Shumen.
Keywords: Countermarks; Lower Danube limes; Roman coins